Børneperspektiver: En vinkel på praksis - Poulsen, Christina Holm (Tidsskrift for Professionsstudier, 2019)
The article focuses on what it means to create a child’s perspective based on an understanding that this perceptive of practice is relevant for researchers and professionals in day care and school. Through practical examples the kind of knowledge created by using a perspective on practice from a child's standpoints, and how this knowledge can be of significance for the development of practice, will be illustrated. The main objective for the article is to show that teachers and researchers can develop relevant knowledge about practice and how children experience their everyday and institutional life by exploring what children are doing together. Thus, the focus on children's actions and participation is pointing to an approach where children's perspective transcends the dominant role of the verbal language. The article argues that it does not require a specific knowledge or specific method to develop knowledge from a child's perspective, but rather a committed and curious companionship with the children.